2020
DOI: 10.1093/geront/gnaa215
|View full text |Cite
|
Sign up to set email alerts
|

Daily Social Interactions and HPA Axis Activity Among Midlife and Older Adults

Abstract: Background and Objectives Older people experience fewer negative interactions and report less stress in response to interpersonal tensions. Less is known, however, about the implications of daily social interactions for biological stress responses. We evaluated links between daily positive and negative interactions and two key biomeasures of the Hypothalamic Pituitary Adrenal (HPA) axis: salivary cortisol and dehydroepiandrosterone sulfate (DHEA-S). We also considered the moderating effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…All other studies found no direct association between CAR, single measurements of cortisol levels at waking-up and number of acute stressors [ 25 , 102 106 ] in general and regarding caregiving of children with fragile X syndrome [ 102 ]. There were also no associations found regarding number [ 107 ] and occurrence [ 108 – 110 ] of acute stressors due to social interactions and severity of acute stressors [ 25 , 104 , 111 ]. However, chronic caregiving stress was suggested to moderate those relationships [ 112 114 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All other studies found no direct association between CAR, single measurements of cortisol levels at waking-up and number of acute stressors [ 25 , 102 106 ] in general and regarding caregiving of children with fragile X syndrome [ 102 ]. There were also no associations found regarding number [ 107 ] and occurrence [ 108 – 110 ] of acute stressors due to social interactions and severity of acute stressors [ 25 , 104 , 111 ]. However, chronic caregiving stress was suggested to moderate those relationships [ 112 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies examining other types of acute stressors found no association with diurnal cortisol slope (i.e. number of acute stressors [ 124 ] number of acute stressors regarding education [ 101 ], social interactions in general [ 101 , 107 ] and discrimination [ 99 ], occurrence of acute stressors in general [ 116 , 125 ] and regarding social interactions [ 110 , 125 ], severity of acute stressors [ 111 ], global subjective stress [ 124 , 126 , 127 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations